Calcium catalyzed enantioselective intramolecular alkene hydroamination with chiral C2-symmetric bis-amide ligands. Issue 9 (17th February 2021) - Stegner, Philipp C.; Eyselein, Jonathan; Ballmann, Gerd M.; Langer, Jens; Schmidt, Jochen; Harder, Sjoerd
Abstract : Enantioselective catalysis with calcium catalysts is challenging due to facile loss of the chiral spectator ligand. Herein a series of bis-amide calcium catalysts with chiral binaphtalene bridges is introduced. Abstract : The chiral building block ( R )-(+)-2, 2′-diamino-1, 1′-binaphthyl, ( R )-BINAM, which is often used as backbone in privileged enantioselective catalysts, was converted to a series of N -substituted proligands R 1 -H2 (R = CH2 t Bu, C(H)Ph2, PPh2, dibenzosuberane, 8-quinoline). After double deprotonation with strong Mg or Ca bases, a series of alkaline earth (Ae) metal catalysts R 1 -Ae·(THF) n was obtained. Crystal structures of these C 2 -symmetric catalysts have been analyzed by quadrant models which show that the ligands with C(H)Ph2, dibenzosuberane and 8-quinoline substituents should give the best steric discrimination for the enantioselective intramolecular alkene hydroamination (IAH) of the aminoalkenes H2 CCHCH2 CR′2 CH2 NH2 (CR′2 = CPh2, CCy or CMe2 ). The dianionic R 1 2− ligand in R 1 –Ae·(THF) n functions as reagent that deprotonates the aminoalkene substrate, while the monoanionic ( R 1 -H) − ligand formed in this reaction functions as a chiral spectator ligand that controls the enantioselectivity of the ring closure reaction. Depending on the substituent R in the BINAM ligand, full cyclization of aminoalkenes to chiral pyrrolidine products as fast as 5 minutes was observed. Product analysis furnished enantioselectivities up to 57% ee, which marks the highest enantioselectivity reported for Ca catalyzed IAH. Higher selectivities are impeded by double protonation of the R 1 2− ligand leading to complete loss of chiral information in the catalytically active species.